Associations of the Dietary Inflammatory Index With Total Adiposity and Ectopic Fat and the Mediating Effect of the Gut Microbiota. (7th June 2021) - Panizza, Chloe; Wilkens, Lynne; Shvetsov, Yurii; Maskarinec, Gertraud; Park, Song-Yi; Shepherd, John; Boushey, Carol; Hebert, James; Wirth, Michael; Ernst, Thomas; Randolph, Timothy; Lim, Unhee; et al.
Abstract: Objectives: To assess, in a large multiethnic cross-sectional study, associations between the Dietary Inflammatory Index (DII®) and total adiposity and ectopic fat, and whether these associations are mediated by gut microbiota (GM). Methods: Analyses used data from 1, 655 participants (812 men, 843 women, 60–77 y) in the Adiposity Phenotype Study. At clinic visit (2013–2015), DXA-based total fat mass, MRI-based visceral adipose tissue (VAT) area at L1-L5 (cm 2 ), and liver fat (% volume) were measured. Participants provided a stool sample and completed a validated food frequency questionnaire (FFQ). Stool bacterial DNA was amplified and the V1-V3 region of the 16S rRNA gene was sequenced. As ratios, GM data were centered log-ratio transformed. DII score was computed from FFQ data, with a higher DII representing a more inflammatory diet. The relationships between DII, GM and adiposity phenotypes were examined using linear regression and mediation analyses. Bootstrap 95% CI were calculated for the indirect effect (IE). Results: DII was positively associated with total fat mass (β = 0.71 kg), VAT (β = 4.73 cm 2 ), and liver fat (β = 0.40%) ( P -values < 0.001). DII was negatively associated with Eubacterium xylanophilum (β = −2.86), and alpha diversity (β = −0.04), and positively associated with Tyzzerella (β = 5.78) ( P -values < 0.001). An inverse relationship was found between E. xylanophilum, VAT (β = −0.11 cm 2 ), and liver fat (β = −0.01%), and between alpha diversity and liver fat (β = −0.93%) ( P -values < 0.001). Tyzzerella was positively associated with VAT (β = 0.04 cm 2 ) ( P < 0.001). The total effect of DII on VAT was partially mediated by E. xylanophilum (IE = 0.30) and Tyzzerella (IE = 0.26). The association between DII and liver fat was partially mediated by E. xylanophilum (IE = 0.02) and alpha diversity (IE = 0.04). GM did not mediate the total effect between DII and total fat mass. Conclusions: The total effect of DII on ectopic fat was partially mediated by lower bacterial diversity and E. xylanophilum, a butyrate-producing genera often inversely associated with inflammation. The association between DII and ectopic fat was also mediated by an abundance of Tyzzerella, a genus previously found to be associated with low-quality diets. Following an anti-inflammatory diet may minimize intra-abdominal fat, in part through the indirect effect of the gut microbiota. Funding Sources: NIH, NCI.